Pengaruh Electronic Word of Mouth (e-WOM) dan Sistem Pembayaran Cash on Delivery (COD) Terhadap Keputusan Pembelian Dalam Perspektif Ekonomi Islam di Marketplace Shopee (Studi Kasus Pada Konsumen Marketplace Shopee di Kota Samarinda) - Mansur, Astri Viana; Parno, Parno; Yanti, Dharma (Borneo Islamic Finance and Economics Journal, 2023)
The Influence of Electronic Word of Mouth (e-WOM) and Cash on Delivery (COD) Payment Systems on Purchasing Decisions in an Islamic Economic Perspective on Shopee Marketplace (Case Study on Shopee Marketplace Consumers in Samarinda City). Thesis, Sharia Economics Study Program, Faculty of Islamic Economics and Business, Aji Muhammad Idris State Islamic University, Samarinda". This research was supervised by Parno, S.E., M.S.I and Dharma Yanti, SE., M.Si. The advancement of the world of technology is growing rapidly, making it easier to buy and sell. The number of marketplaces that are often used by consumers and producers to buy and sell online. Electronic Word of Mouth (e-WOM) communication provides information about the product to be purchased from consumer experience. The Cash on Delivery (COD) payment system is a payment method that provides convenience and security. This study aims to determine the effect of Electronic Word of Mouth (e-WOM) and the Cash on Delivery (COD) payment system on purchasing decisions in an Islamic economic perspective in the Shopee marketplace. The population in this study were Shopee marketplace consumers in Samarinda City. The type of research used is quantitative research. The number of samples in this study were 96 respondents with non probability sampling technique with purposive sampling method. Data analysis using multiple linear regression and hypothesis testing. The results of this study show that Electronic Word of Mouth (e-WOM) partially affects purchasing decisions in an Islamic economic perspective on the Shopee marketplace, Cash on Delivery (COD) partially affects purchasing decisions in an Islamic economic perspective on the Shopee marketplace, and Electronic Word of Mouth (e-WOM) and Cash on Delivery (COD) simultaneously affect purchasing decisions in an Islamic economic perspective on the Shopee marketplace.